The Non-Psychological Conditions that Influence the Acceptance of Violence on Domestic Violence Victims: A Narrative Review - Alizamar Alizamar; Afdal Afdal; Nurmaida Pane (Universitas Negeri Padang, 2019)
Cases of domestic violence that occur in Indonesia have increased every year, one of the causes is due to the patriarki culture that is still inherent in society, where men are considered superiority over women. This condition makes women vulnerable to become victims of domestic violence. Other conditions that cause a person to accept violence are caused by economic, educational, socio-cultural, infidelity, and third-party interference. This article aims to provide an overview of non-psychological conditions that affect the acceptance of violence in victims of domestic violence by using the method of literature study as well as the approaches that can be done by counselors discussed further.